Analysis of microbial communities in wheat, alfalfa, and oat crops after Tilletia laevis Kühn infection - Shen, Yuyang; Delai, Chen; Liu, Taiguo; Chen, Wanquan; Li, Guangkuo; Gao, Haifeng; Gao, Li (Frontiers in Microbiology, 2024)
Common bunt caused by Tilletia laevis Kühn is one of the most serious fungal diseases of wheat. The root–microbial associations play key roles in protecting plants against biotic and abiotic factors. Managing these associations offers a platform for improving the sustainability and efficiency of agriculture production. Here, by using high throughput sequencing, we aimed to identify the bacterial and fungal associations in wheat, alfalfa, and oat crops cultivated in different years in the Gansu province of China. Soil samples (0–6 cm below the surface) from infected wheat by T. laevis had significantly more bacterial and fungal richness than control samples as per the Chao1 analysis. We found some dominant fungi and bacterial phyla in infected wheat by T. laevis, such as Proteobacteria, Acidobacteria, Actinobacteria, Chloroflexi, Ascomycota, Basidiomycota, and Mortierello mycota. We also analyzed the chemical and enzymatic properties of soil samples after T. laevis inoculation. The total nitrogen, total kalium (TK), ammonium nitrogen, available kalium, organic carbon, invertase, phosphatase, and catalase were more in T. laevis-infected samples as compared to the control samples, while pH, total phosphorus, nitrate nitrogen, available phosphorus, and urease were more in control samples compared to T. laevis-infected samples. The results of this study will contribute to the control of wheat common bunt by candidate antagonistic microorganisms and adverse properties of soil.